Student Facilitator and Explaining Model in The Development of HRH in the UPTD Puskesmas Hilisataro, Nias Selatan District - Sri Rahmat Wati Wau; Sri Lestari Ramadhani Nasution; Ermi Girsang (Jurnal Scientia, 2024)
The Hilisataro Health Center in South Nias Regency has Healthy health human resources who are less able to think in a systemic way to see problems as an opportunity to take one step further. This study aims to analyze health human resources development strategies using the student facilitator and explaining model. This type of research was Quasy–Experimental (pre–experimental designs) conducted at the UPTD Health Center Hilisataro South Nias Regency in December 2022. The sample in this study was all health human resources at the UPTD Health Center Hilisataro South Nias Regency, totaling 102 people. The data were analyzed using the t-test. The results of the univariate study showed that of the 102 respondents studied, it was found that the majority of respondents were aged 36-45 years, namely 40 (39.2%) respondents, female, 59 (57.9%), D3 educated, 58 ( 56.8%). The results of the t-test show that there is an impact of the student facilitator and explaining the strategy model on increasing health human resources knowledge. There is an impact of the strategy of the student facilitator and explaining model on health human resources creativity and innovation. There is an impact of the student facilitator and explaining model strategy on the use of technology by health human resources. There is an impact of the strategy of the student facilitator and explaining model on the ability of the health human resources to express opinions. There is an impact of the strategy of the student facilitator and explaining model on the critical thinking of health human resources through the strategy at the UPTD of the Hilisataro Health Center, South Nias Regency. Based on the results of the research, it is suggested that the leadership of the puskesmas can be responsible for determining program management policies to improve services at the puskesmas by conducting trainings that can improve health human resources performance.